Implementasi Pelatihan Sadar Wisata Bahari Berbasis Karakter di Pantai Cemara Kabupaten Bireuen - Novalita, Rahmi; Sumanti, Sumanti; Carvina, Mona (LPPM Umuslim, 2024)
Bireuen Regency has many tourist attractions that are worth visiting by the public. The tourist attractions in Bireuen are very good and worth visiting by tourists, but tourists and visitors are reluctant to visit several tourist attractions in Bireuen for several reasons. One aspect of tourism development is tourism awareness. Tourism awareness is community participation in creating tourist areas in accordance with the seven charms of tourist attractions. Lecturers and students of Almuslim University tried to carry out community service activities at the Cemara Beach tourist attraction in the form of community service activities, namely